2000
DOI: 10.1021/ie9903588
|View full text |Cite
|
Sign up to set email alerts
|

Subcolloidal Fe/Ag Particles for Reductive Dehalogenation of Chlorinated Benzenes

Abstract: Subcolloidal (<0.1 μm) iron−silver (1% Ag) particles were synthesized for the transformation of chlorinated benzenes in aqueous solution. Hexachlorobenzene (HCB) (4 mg/L) was dechlorinated to tetra-, tri-, and dichlorobenzenes (TeCB, TCB, and DCB, respectively) within 24 h at a metal loading of 25 g/L. Principal degradation products included 1,2,4,5-TeCB, 1,2,4-TCB, and 1,4-DCB. Continuous dechlorination was observed during a 57-day experiment. The rate of dechlorination was positively correlated to the silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
123
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(126 citation statements)
references
References 32 publications
2
123
0
1
Order By: Relevance
“…[26][27][28] The average size of the Fe NPs is 25 nm with diameter ranging from 5-60 nm and a surface to weight ratio of 40-60 m 2 /g. The packing density is 0.10-0.25 g/cm 3 .…”
Section: Experimental Chemicals and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] The average size of the Fe NPs is 25 nm with diameter ranging from 5-60 nm and a surface to weight ratio of 40-60 m 2 /g. The packing density is 0.10-0.25 g/cm 3 .…”
Section: Experimental Chemicals and Reagentsmentioning
confidence: 99%
“…[15] Nanoparticles (NPs) have been extensively investigated and applied to biochemical applications due to their large surface area to volume ratios and high surface reactivity. [26][27][28] The Fe NPs exhibit tens to hundreds times more surface reactivity than that of micro-or milli-scale Fe particles. [26][27][28] In this study, we first observed the (H 2 O) 20 O þ oxygenated water cluster ions (m/z 376) by introducing a suspension of Fe NPs in solution into an electrospray ionization mass spectrometry (ESI-MS) system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…nZVI easily reduce organic compounds such as chlorinated ethenes [4][5][6][7][8], chlorinated ethanes [9], chlorobenzenes [10], pesticides [3], PCB [11,12]. Inorganic substances include several anions such as nitrate, phosphate and sulphate [3] and in particular heavy metals such as Cr, As, Pb and U [13][14][15] can be also stabilized by nZVI.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand smaller proportions of organic polar solvents have been used in aqueous reaction phase for lab scale studies. For example, Liu et al [30], Roy et al [31], Kim and Carraway [16], Xu and Zhang [32], and Doong and Rai [33,34] used acetone and methanol in various proportions (1, 0.2, 0.5, 0.05% v/v) to prepare solutions of chlorinated compounds such as, chlorophenols, PCP, chlorobenzenes, and trichloroethylene (TCE). However, the fore-mentioned publications do not provide any justification for the selection of a co-solvent or its concentration.…”
Section: Introductionmentioning
confidence: 99%